The effects of collective bargaining on firm performance: New evidence based on stochastic production frontiers and multiply imputed German establishment data - Uwe Jensen; Susanne Rässler (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2007)
This paper makes three contributions to the literature on the effects of collective bargaining on the performance of German establishments. We include the analysis of firms efficiency and we model productivity and efficiency simultaneously. Confronted with 25 % observations with missing values, we check the missing data mechanisms and find effects of firm size and collective bargaining on it, among others. After proper multiple imputation of the missing values thus avoiding obvious nonresponse bias , the results on the collective bargaining effects on productivity and efficiency change significantly. Finally, we suggest to multiply impute implausible zero values in the capital proxy as well.
Keywords: C15; C24; C81; D24; J50; 330; Tarifverhandlungen; Lohnpolitik; Produktivitätseffekte; Unternehmenserfolg; IAB-Betriebspanel; Schätzung; Fehler; Datenaufbereitung; angewandte Statistik; Tarifpolitik; Unternehmensentwicklung; Produktivität; Technische Effizienz; Schätzung; Deutschland